Methylenedioxyamphetamine (MDA) and methylenedioxymethamphetamine (MDMA) cause selective ablation of serotonergic axon terminals in forebrain: immunocytochemical evidence for neurotoxicity - O'Hearn, E (J Neurosci, 1988)
The psychotropic amphetamine derivatives 3,4-methylenedioxyamphetamine (MDA) and 3,4-methylenedioxymethamphetamine (MDMA) have been used for recreational and therapeutic purposes in man. In rats, these drugs cause large reductions in brain levels of serotonin (5-HT). This study employs immunocytochemistry to characterize the neurotoxic effects of these compounds upon monoaminergic neurons in the rat brain. Two weeks after systemic administration of MDA or MDMA (20 mg/kg, s.c., twice daily for 4 d), there is profound loss of serotonergic (5-HT) axons throughout the forebrain; catecholamine axons are completely spared. Regional differences in drug toxicity are exemplified by partial sparing of 5-HT axons in hippocampus, lateral hypothalamus, basal forebrain, and in some areas of neocortex. The terminals of 5-HT axons are selectively ablated, while axons of passage and raphe cell bodies are spared. Thickened preterminal fibers exhibit increased staining due to damming-up of neurotransmitter and other axonal constituents. Fine 5- HT axon terminals are extremely vulnerable to these drugs, whereas terminal-like axons with large varicosities survive, raising the possibility that some 5-HT axons may be resistant to the neurotoxic effects. At short survivals, visualization of greatly swollen, fragmented 5-HT axons provides anatomic evidence for degeneration of 5- HT projections. The results establish that MDA and MDMA produce structural damage to 5-HT axon terminals followed by lasting denervation of the forebrain. Both drugs have similar effects, but MDA produces a greater reduction of 5-HT axons than does MDMA at the same dosage. The selective degeneration of 5-HT axons indicates that these drugs may serve as experimental tools to analyze the organization and function of 5-HT projections. Caution should be exercised until further studies determine whether these compounds may be hazardous in man.